Fronto-occipital dyscommunication associates with brain hierarchy in schizophrenia - Haonan Pei; Hechun Li; Changyue Hou; Yayun Liu; Jiashuo Liu; Mingjun Duan; Dezhong Yao; Sisi Jiang; Cheng Luo (Communications Biology)
Abstract Schizophrenia involves abnormal fronto-occipital interactions linked to hallucinations and cognitive impairments, but the neural mechanisms remain unclear. This work aims to provide an overview of the relationship between fronto-occipital dysfunction and symptoms using simultaneous EEG-fMRI data in schizophrenia. We measured the brain’s functional separation and quantified bidirectional information transfer changes between the frontal and occipital regions. A pronounced elevation in correlation within the frontal lobe, accompanied by a marked reduction in the occipital lobe, was observed between gradient eccentricities and theta-power of forward waves. Moreover, the relationship between forward waves and gradient eccentricities in the ventrolateral prefrontal cortex may be shaped by positive symptoms, while the influence of negative symptoms appears to modulate the relationship between backward waves and gradient eccentricities in the insula. The MOR and CB1 neurotransmitters predominantly contributed to associations between eccentricities and traveling waves. Symptoms promote the dysregulation of hierarchical separation and information transmission in schizophrenia.